A comparative study of the business practices of Filipino and Chinese entrepreneurs engaged in merchandising business in Iloilo City - Bakabak, Sheila Mae; Cuan sing, Crispy Ann; Descuatan, Lynn; Juanico, Richelle; Prieto, Janice
Using questionnaire, Filipino and Chinese entrepreneurs were evaluated to determine the similarities and differences in their business practices. No significant differences were found in the savings and spending pattern, degree of involvement in the business and risk-taking attitudes between Filipino and Chinese. However, a significant relationship existed between the ethnic groups and their major strengths and success rate. The researchers recommend that Filipino should try to venture into merchandising business wherein they have potentials to succeed, despite the fact that such kind of business is dominated by the Chinese. Consideration of other factors in the determination of success and the reasons for the dominance of the Chinese in merchandising business are some recommendations for further research in the future.